Bronze goods as a reflection of the ethnocultural ties of the South Caucasus peoples in ancient times - Sevda T. Samedova (Историческая этнология)
The object of the study are ancient bronze goods discovered in the South Caucasus as a result of archaeological excavations at the sites of ancient settlements and burial grounds of the Bronze and early Iron Ages. Among the various types of bronze jewelry, bracelets were the most numerous and functionally in demand, as they were used simultaneously as decoration and amulets. There is an opinion that they were an equivalent of money and served as a means of commodity-money exchange. In the era of antiquity, in the region, jewelers continued to produce bronze jewelry along with jewelry made of silver and gold. Commonly found jewelry made of silver and gold were compositionally close or identical to bronze jewelry. In the antique layers of the region, bronze jewelry is found in all types of burial grounds. At that time, weapons and tools began to be made of iron. In addition to bracelets, other types of bronze jewelry have been identified – various pendants, rings, neck jewelry, and numerous buckles. The study identifies jewelry that is similar in parameters (technique of execution, metal composition, style of form and decoration), which was found during archaeological excavations located distant from each other. The objective of the study is to conduct the comparative analysis of the identified local artifacts with artifact decorations that are generally similar within the region; to reflect such aspects of these goods as form, type and elements of ornamentation, raw material base of products, which indicate ethnocultural contacts of the population of the region.